Exploring Risk Management, Disruptions, and Recovery Strategies in the Chemical Manufacturing Sector in South Africa - Anathi, Sokhetye; Makalima, Mzuchumile (Acta Carolus Robertus, 2025)
This study explores risk management, disruptions, and recovery strategies within the chemical Manufacturing companies in South Africa. The emphasis of the investigation is on finding out how risks are identified and assessed by enterprises, and their strategies for mitigating them or recovering from interruptions. Based on semi-structured interviews with business executives, it explores the responses of internal factors and external risk factors, like regulatory changes, labour unrest, natural disasters, and global pandemics such as COVID-19, to alter risk management behaviors. The results indicated that larger firms indeed had more sophisticated risk assessment techniques, but smaller companies were indeed catching up with digital tools to enhance their risk management. In this study, the three most important means for reducing risk and allowing speedy recovery were identified: supply chain diversification, technology, and flexibility of the workforce. firms with more developed information systems could adapt more readily to disruptions, further emphasizing the role of real-time data for operational resilience. It also deduces the relevance of constant adjustments to dynamically alter the external environment, particularly the socio-politically volatile ones. The contributions of this paper are that an understanding of how risk management will be handled can be enhanced and practical insights have been offered through which business sustainability against future interruptions can be assured in South African chemical manufacturing industries.